Remittance Stability, Cyclicality and Stabilizing Impact in Developing Countries - Neagu, Ileana C.; Schiff, Maurice (2012)
That remittances are a stable source of external finance seems to have become the received wisdom. In addition, many studies have found remittances to behave counter-cyclically, increasing during crises and times of hardship for the recipient countries. Are remittances reliable macroeconomic stabilizers? To answer this question, the present study examines the stability, cyclicality, and stabilizing impact of remittances in comparison with the same three features for other foreign-exchange inflows, namely foreign direct investment and official development aid. The analysis is performed at the country and regional levels rather than at the aggregate or global level (on which much of the received wisdom rests), because policymakers are concerned with the impact of remittances in their country rather than at the global level. The main findings for 1980-2007 are that in a majority of countries: i) official development aid is more stable than remittances, and remittances are more stable than foreign direct investment; ii) official development aid is counter-cyclical, while remittances are pro-cyclical, although less so than foreign direct investment; and iii) official development aid is stabilizing and remittances are destabilizing, although less so than foreign direct investment. The paper suggests that it is necessary to examine counter-cyclicality separately from the stabilizing impact, as the former does not seem to always imply the latter.